A rare cause of stroke at a young age: ischemic stroke by the mechanism of paradoxical embolism in a patient with hereditary hemorrhagic telangiectasia - A. V. Belopasova; P. S. Shlapakova; L. A. Dobrynina; A. S. Kadykov (Неврология, нейропсихиатрия, психосоматика, 2023)
Clarification of the aetiology of ischemic stroke (IS) in young adults (aged between 18 and 45 years) is an extremely difficult task, as rare causes that are hardly known to neurologists are very common. One of these causes is paradoxical embolism due to pulmonary arteriovenous malformation (AVM), one of the manifestations of hereditary hemorrhagic telangiectasia (HHT). The diagnosis of HHT-associated pulmonary AVMs and IS is a multistep task that requires a personalized multidisciplinary approach using high-tech ultrasound, tomographic and genetic examination methods. This article discusses the clinical case of a young patient with HHT and recurrent IS through the mechanism of paradoxical embolism from pulmonary AVMs; issues of diagnosis, treatment and prevention of both the underlying disease and recurrent vascular events are discussed.